Pengaruh tata kelola perusahaan dan karakteristik spesifik perusahaan pada kejadian penyajian kembali laporan keuangan - Susanto, Androni; Syahputri, Dhea Ananda (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Financial statements are a means of communication between the activities of the company and the parties with an interest in the company. This study aims to analyze the effect of corporate governance as measured by board size, board independence, audit committee finance, audit quality, and company-specific characteristics as measured by firm size, ROA, leverage, and liquidity on the restatement of financial statements. The research method used is a quantitative method. There are 513 financial and non-financial companies listed on the Indonesia Stock Exchange during the 2017–2021 period, but 14 companies that do not meet the criteria for the research sample are 499 companies. The results of this study are that the formation of restatements, with a total of 122 and 229 non-restatements during the 2017–2021 period. This research says that the size of the company and the leverage of the company can influence the financial restatement events. There is an important positive relationship between firm size and financial restatement events. The size of a company can determine the size of a company. The size of the company affects the restatement of financial statements, because the bigger the company, the easier the transactions will be.